169 Impact of Low-Intensity Extracorporeal Shock Wave Therapy on Sexual Function after Non-Nerve-Sparing Robot-Assisted Laparoscopic Radical Prostatectomy. (1st May 2022) - Inoue, S.; Hayashi, T.; Teishima, J.
ABSTRACT: Objective: Considering the natural course of cavernous nerve recovery following robot-assisted laparoscopic radical prostatectomy (RARP), early intervention of low-intensity extracorporeal shockwave therapy (LIESWT) would be more effective for enhancing overall recovery of potency. We analyzed longitudinally alterations in sexual function in patients after RARP, with focus on the effect of early and delayed intervention with LIESWT. Method: This study was open-label prospective study. Four patients after RARP were enrolled into this study's protocol over a period between January and June 2017. This early intervention was performed three times a week for two weeks in admission and one time per week in our out patient clinic for six weeks. For the purpose of setting a control group, the same surgeon performed RARP on 4 patients over a period between June 2012 and December 2014. These patients received LIESWT and this delayed protocol was same as that by Vardi et al. The same surgeon performed RARP on 100 patients over a period between April 2012 and February 2015. These patients were assigned to the non-LIESWT group for setting another control group. Sexual function (SF) was assessed with the Expanded Prostate Cancer Index Composite (EPIC). A validated form of self-reported questionnaire was administered to the inpatients before RARP, and mailed to all patients receiving RARP at 3, 6, 9, and 12 months after RARP. Results: There was no significant inter-group difference in the baseline patient characteristics and surgical outcomes. The mean duration from RARP to the start of penile rehabilitation was 6 months for patients of the delayed LIESWT group. The SF score was significantly higher at preoperative, postoperative 6 and 9 months (p=0.0024, 0.0001, and 0.0004) in the early-LIESWT group. The SF score of early-LIESWT was significantly higher than that of delayed-LIESWT at postoperative 6 and 9 months (19.7 vs. 7.4; p = 0.0153, 26.2 vs. 6.1; p = 0.0154). On the other hand, there was no significant difference in the SF score between delayed and non-LIESWT groups at all time points. Conclusions: Our findings show that penile rehabilitation with LIESWT immediately before urethral catheter removal improved sexual function scores. Our preliminary results suggest that LIESWT could be used as a treatment option in penile rehabilitation. Disclosure: Work supported by industry: no.